Adult Age Differences in Using Information From the Eyes and Mouth to Make Decisions About Others' Emotions. (10th August 2022) - Slessor, Gillian; Insch, Pauline; Donaldson, Isla; Sciaponaite, Vestina; Adamowicz, Malgorzata; Phillips, Louise H
Abstract: Objectives: Older adults are often less accurate than younger counterparts at identifying emotions such as anger, sadness, and fear from faces. They also look less at the eyes and more at the mouth during emotion perception. The current studies advance understanding of the nature of these age effects on emotional processing. Methods: Younger and older participants identified emotions from pictures of eyes or mouths (Experiment 1) and incongruent mouth–eyes emotion combinations (Experiment 2). In Experiment 3, participants categorized emotions from pictures in which face masks covered the mouth region. Results: Older adults were worse than young at identifying anger and sadness from eyes, but better at identifying the same emotions from the mouth region (Experiment 1) and they were more likely than young to use information from the mouth to classify anger, fear, and disgust (Experiment 2). In Experiment 3, face masks impaired perception of anger, sadness, and fear more for older compared to younger adults. Discussion: These studies indicate that older people are more able than young to interpret emotional information from the mouth, they are more biased to use information from the mouth, and suffer more difficulty in emotion perception when the mouth is covered with a face mask. This has implications for social communication in different age groups.